Popular Leadership Style in Local Bureaucracy - Erika Juniar; Singgih Tiwut Atmojo; Liza Aswati (STKIP Singkawang, 2019)
The purpose of this study was to find leadership style popular (autocratic, laissez-faire, paternalistic, charismatic and democratic) on employee work discipline at Dinas Lingkungan Hidup Singkawang City. In this study, using a form of qualitative research. The method of data collection consisted of primary data (observations, and questionnaires). The population of this study was the employes in Dinas Lingkungan Hidup Singkawang City, and the sample is all populations made into samples. This study concluded that together or simultaneously leadership style has an influence on employee work discipline of the Dinas Lingkungan Hidup Singkawang City, with a significance of 0.004 < 0.05. Four of the five independent variables proved influential on work discipline, the variable is autocratic, laissez-faire, charismatic, and democratic. The conclusion of this study was that what was felt by employees of Dinas Lingkungan Hidup Singkawang City that the popular leadership style in their opinion was style autocratic, laissez-faire, charismatic and democratic style.